Use of methodological strategies to improve english learning process in hildrenwith attention deficit hyperactivity disorder from sixth graders at centro educativo miraflores school - Maldonado Bermudes, Joseph Jonathan (2016)
The main purpose of this research project is to improve the English learning process in students with ADHD through methodological strategies in sixth grade students at Centro Educativo Miraflores. To achieve this goal, the objectives were established to determine the methodological strategies that can be applied to improve the English learning process in students with this disorder. As a part of this process, class observation, surveys, interview to teachers, principal and parents to know the difficulties and deficiencies that they are facing. Later on, analyzing and comparing the data obtained with the instruments, there were many factors that affected the English learning process in these students with ADHD. The development of methodological strategies was one of the important aspects, most of them had to deal with the poor knowledge that teachers had at the moment of dealing with them. After working with teachers and students with ADHD, we created a better environment and got a good experience in class using the methodological strategies. Finally, we concluded making some recommendations for the institution in order to improve the English learning process in students with ADHD….